Front Matter - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
The prelims comprise: Half-Title Page Title Page Copyright Page Table of Contents Author Biographies Foreword Symbols and Abbreviations